Neuroprotective Potency of Neolignans in Magnolia officinalis Cortex Against Brain Disorders - Zhu, Shun; Liu, Fang; Zhang, Ruiyuan; Xiong, Zongxiang; Zhang, Qian; Hao, Li; Chen, Shiyin (Frontiers in Pharmacology, 2022)
In recent years, neurological diseases including Alzheimer's disease, Parkinson's disease and stroke are one of the main causes of death in the world. At the same time, the incidence of psychiatric disorders including depression and anxiety has been increasing. Accumulating elderly and stressed people suffer from these brain disorders, which is undoubtedly a huge burden on the modern aging society. Neolignans, the main active ingredients in Magnolia officinalis cortex, were reported to have neuroprotective effects. In addition, the key bioactive ingredients of neolignans, magnolol (1) and honokiol (2), were proved to prevent and treat neurological diseases and psychiatric disorders by protecting nerve cells and brain microvascular endothelial cells (BMECs). Furthermore, neolignans played a role in protecting nerve cells via regulation of neuronal function, suppression of neurotoxicity, etc. This review summarizes the neuroprotective effect, primary mechanisms of the leading neolignans and provides new prospects for the treatment of brain disorders in the future.